A Phenomenological Study to Explore the Lived Experience of Patient Living with Mental Illness - S. Veera Jyothi; Rajeshree Lokhande; Chris Thomas (Indian Journal of Psychiatric Nursing)
Background: A broad understanding of patient’s mental health problem is important to deliver effective and patient-centered mental health interventions. Patients with mental illness feel frustrated when they will not be listened by the health professional. People living with mental illness have different problems which are unheard by the society because of various stereotypes regarding mental illness. Objective: The objective of this study was to describe the experience of the patient living with mental illness. Methodology: The research approach used was qualitative and the research design was hermeneutic phenomenological design. With the help of purposive sampling technique, the data were collected from 20 patients through the interview technique. Results: The study results were described into three emergent themes such as patient’s perception about the cause of their mental illness, patient’s experience of their symptoms, and patient’s understanding of their positive and negative experiences of their treatment. Conclusion: The study indicated that mentally ill persons experience many changes in their lives but manage to develop coping skills. Patients had both positive and negative experiences while living with mental illness. The experience of stigma and discrimination, dependence on prescribe medication and its related side effects, loss, and fear, all contributed to the hazy reality of living with mental illness.